The effect of brief digital mindfulness-based interventions on increasing online charitable behavior in Chinese adolescents - Hong, Mei; Liang, Dapeng; Lu, Teng; Liu, Shengchen (Frontiers in Psychology, 2023)
Digital mindfulness-based interventions (d-MBIs) have garnered significant research interest in recent years due to their psychological benefits. However, little is known about their impact on prosocial behaviors. This study investigates how d-MBIs impact prosocial behaviors where time spent is money, with Chinese adolescents as the subjects, through an online charity task (www.freerice.com). 119 students from a high school in China, who were inexperienced with mindfulness meditation, participated in this randomized controlled trial. The d-MBI group (N = 39) received online MBI guidance, while the face-to-face mindfulness-based intervention (f-MBI, N = 43) group underwent mindfulness intervention under personal tutors. The active control group (N = 37) completed a crossword task. Data analysis first involved repeated measures variance analysis, including pre-and post-intervention assessments. Subsequently, a two-way variance analysis was performed, with gender (female and male) and group (d-MBI, f-MBI, active control) as independent variables and the number of grains as dependent variables for the three groups of participants. Results showed that d-MBIs effectively improved empathy and compassion in Chinese adolescents, leading to increased rice donations to the United Nations World Food Program. These results underscore the positive effect of d-MBIs on prosociality and suggest their applicability in beneficial real-world situations involving prosocial behaviors, extending beyond previous research primarily conducted in artificial and hypothetical scenarios.